CURRICULUM MANAGEMENT ANALYSIS IN IMPROVING THE QUALITY OF PERFORMANCE OF EDUCATORS AND EDUCATION PERSONNEL - Mohamad Kamil Salas; Masluhah (International Journal of Teaching and Learning, 2025)
This study aims to analyze the role of curriculum management in improving the quality of educator and education personnel performance. Curriculum management includes planning, implementation, monitoring, evaluation, and ongoing curriculum adjustment. Effective curriculum management plays a significant role in improving the quality of educator and education personnel performance. Systematic curriculum planning provides a clear direction for educators in implementing learning. Continuous professional training and development helps educators master effective learning strategies that are relevant to student needs. In addition, support for facilities and infrastructure, as well as the use of technology in learning, are also important factors that support improved performance. Periodic performance evaluations provide constructive feedback, so that educators and education personnel can continue to improve their competence. This study concludes that well-implemented curriculum management can create a conducive learning environment, support the achievement of educational goals, and empower educators and education personnel to contribute optimally to the educational process.